2017
DOI: 10.1590/0104-6632.20170344s20150660
|View full text |Cite
|
Sign up to set email alerts
|

An entirely renewable biofuel production from used palm oil with supercritical ethanol at low molar ratio

Abstract: -The biofuel production from used palm oil (UPO) using supercritical ethanol (SCE) at low molar ratio was investigated in order to produce an entirely renewable fuel. The effects of the reaction time and ethanol to oil molar ratio were considered from 0.5 to 10 min and 6:1 to 18:1, respectively. The optimal parameters were 10 min and a 12:1 molar ratio, representing a remarkable reduction from 42:1 for the conventional SCE process. Because of the high operating temperature, the triglycerides conversion rate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Gaurav et al [15] demonstrated that canola oil was reported as having palmitic, oleic and linoleic acid. Sakdasri et al [36] used waste palm oil from a restaurant and Giraçol et al [37] studied cooking soybean oil residues from homes for biodiesel production. Moreover, other residues, such as municipal wastewater, can be utilized to grow oleaginous algae commonly used for biodiesel production [32].…”
Section: Urban Wastesmentioning
confidence: 99%
“…Gaurav et al [15] demonstrated that canola oil was reported as having palmitic, oleic and linoleic acid. Sakdasri et al [36] used waste palm oil from a restaurant and Giraçol et al [37] studied cooking soybean oil residues from homes for biodiesel production. Moreover, other residues, such as municipal wastewater, can be utilized to grow oleaginous algae commonly used for biodiesel production [32].…”
Section: Urban Wastesmentioning
confidence: 99%
“…2014), tung tree (Aleurites spp.) (CHEN et al, 2010;SHANG et al, 2010;SHARMA et al, 2011;ZORNITTA et al, 2017), sunflower seed (KNOTHE et al, 1997;REFAAT et al, 2008), rubber seed (KANT et al, 2011;RAMADHAS et al, 2004), jojoba (Simmondsia chinensis) (BORUGADDA & GOUD, 2012), oil palm (CHEAH et al, 2016;SAKDASRI et al, 2017), neem (Azadirachta indica) (ANYA et al, 2012;ARANSIOLA et al, 2012), sugarcane (Saccharum oficinarum) (BRIENZO et al, 2015;ISMAIL & ALI, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, such feedstock types do usually have higher FFA content, which make them unsuitable for the conventional catalyst technologies. Even though the other alternative technologies such as acid catalysts, enzyme catalysts, supercritical alcohol, could not be well applied at industrial scale, they are proved to be efficient in producing fuel quality biodiesel from low‐cost feedstock with considerable FFA content 4–6 . Acid catalysts could help to catalyze esterification and transesterification reactions simultaneously; in this way there would be more biodiesel produced than using most other catalyst technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the other alternative technologies such as acid catalysts, enzyme catalysts, supercritical alcohol, could not be well applied at industrial scale, they are proved to be efficient in producing fuel quality biodiesel from low-cost feedstock with considerable FFA content. [4][5][6] Acid catalysts could help to catalyze esterification and transesterification reactions simultaneously; in this way there would be more biodiesel produced than using most other catalyst technologies. The heterogeneous acid catalysts do have additional advantages of easy recovery from the process for possible reuse a number of times.…”
mentioning
confidence: 99%